2017
DOI: 10.1002/jcp.26060
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐mediated drug resistance in ovarian cancer

Abstract: The development of intrinsic or acquired resistance to chemotherapeutic agents used in the treatment of various human cancers is a major obstacle for the successful abolishment of cancer. The accumulated efforts in the understanding the exact mechanisms of development of multidrug resistance (MDR) have led to the introduction of several unique and common mechanisms. Recent studies demonstrate the regulatory role of small noncoding RNA or miRNA in the several parts of cancer biology. Practically all aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 107 publications
(143 reference statements)
0
49
0
Order By: Relevance
“…miRNAs pair imperfectly with the 3′-untranslated region (3′UTR) of specific mRNAs to regulate the transcriptional and post-transcriptional expression of target genes (6). Mounting evidence has demonstrated that miRNAs are involved in numerous physiological and pathological processes (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs pair imperfectly with the 3′-untranslated region (3′UTR) of specific mRNAs to regulate the transcriptional and post-transcriptional expression of target genes (6). Mounting evidence has demonstrated that miRNAs are involved in numerous physiological and pathological processes (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…They play an important regulatory role in the expression of genes in both animals and plants [11]. In the case of miRNA, the regulation of gene expression takes place at the post-transcriptional level and involves interaction with mRNA [12]. The seed sequence (6-8 nucleotides) located in the 5' region of the miRNA plays a key role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…5 Thus, drug resistance is a major clinical problem, and understanding its mechanisms and identifying its predictive biomarkers are ongoing needs. [7][8][9] Regardless of the factors, dysregulated genes are closely associated with drug resistance and prognosis in OC. [7][8][9] Regardless of the factors, dysregulated genes are closely associated with drug resistance and prognosis in OC.…”
Section: Introductionmentioning
confidence: 99%